KEMANDIRIAN KEUANGAN DAERAH PROVINSI DAERAH ISTIMEWA YOGYAKARTA DAN KABUPATEN /KOTA DI DAERAH ISTIMEWA YOGYAKARTA - , Lia Ekowati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Implementation of regional autonomy and fiscal decentralization provide important implications for the performance of the regional economy. The financial performance of the region is a real picture of the local financial independence should be the level of dependence on the central government has declined or increased local financial independence. However, the financial independence of local government development tends to decrease. This is not in line with the objectives of fiscal decentralization. The research method is quantitative descriptive techniques through documentation with descriptive statistical data analysis. Level of financial independence of D.I Yogyakarta region as measured by the degree of fiscal decentralization is better that the average is 49,05% (PAD/TPD), 45,63% (SUM/TPD) and 5,32% (BHPBP/TPD). While the District or City of D.I Yogyakarta is still high dependence on the central government finances are on average below 10,10% (PAD/TPD and either BHPBP/TPD) and above 70% (SUM/TPD). Fiscal capacity of the district or city can not meet the fiscal needs, although its value despite the high standard of provincial fiscal capacity of D.I Yogyakarta. Tax Effort to assess the elasticity of fiscal revenue to GDP result is quite good. Changes that occur at the district or city affect the province, and vice versa. Provincial and district or city is a part that can not be separated from each other and influence each other. Financial policies defined area countries or cities will affect the financial condition of the province. Local government capacity to explore, analyze, process, evaluate and supervise the financial resources or PAD is low quality and quantity. Provincial government in particular districts or cities in D.I Yogyakarta need to increase revenue through tax revenues, retribution, enterprises (BUMD), regional cooperation, and improvement of the quality and quantity of apparatus